Pelatihan Guru Penggerak Dan Pendekatan Pembelajaran Mendalam (Deep Learning) Guru SMP Muhammadiyah PCM Kartasura - Wachidi Wachidi; Ma’arif Jamuin; Nurul Latifatul Inayati; Eko Wicaksono; Alfan Rifa’i Abu Suheil (Easta Journal of Innovative Community Services, 2026)
This community service program aims to enhance the competence of teachers at SMP Muhammadiyah in PCM Kartasura through socialization and training on the Teacher Driver program and Deep Learning approach. The main objectives of this program are to ensure that teachers gain knowledge, skills, and attitudes related to the concepts of Teacher Driver and Deep Learning. It is expected that teachers will apply innovative teaching approaches and improve the quality of education at Muhammadiyah schools. This program also seeks to strengthen educational leadership at the school level, given the limited access to Teacher Driver training for private schools and the lack of understanding about Deep Learning in the PCM Kartasura area. This initiative is driven by the importance of the Teacher Driver program in creating learning leaders capable of implementing the Merdeka Curriculum and addressing challenges in education quality. The program is implemented in several phases, starting with socialization and training, followed by teachers formulating action plans, which are then implemented at their respective schools. After implementation, monitoring and evaluation are conducted to assess the program's effectiveness. The outcomes of this program are expected to improve teachers' competence, values, and attitudes in managing learning and supporting educational innovation at Muhammadiyah schools in PCM Kartasura. The results will be documented in an evaluation report and scientific publications, contributing to the development of education in the region.